Persuasive Technology and computational manipulation: hypernudging out of mental self-determination - Faraoni, Stefano (Frontiers in Artificial Intelligence, 2023)
Artificial Intelligence, unperceived, can acquire the user’s data, find connections not visible by a human being, profile the users, and aim at persuading them, resulting in Persuasive Technology (PT). During the persuasive process, PT can use manipulation, finding and using routes to affect System 1, the primordial brain of individuals, in the absence of their awareness, undermining their decision-making processes. Multiple international and European bodies recognised that AI systems could use manipulation at an unprecedented degree via second-generation dark patterns such as the hypernudge and that computational manipulation constitutes a risk for autonomy and different, overlapping, fundamental rights such as privacy, informational self-determination and freedom of thought. However, there is a lack of shared ideas regarding which fundamental rights are violated by computational manipulation and which fundamental rights can protect individuals against it. The right to be let alone and the right to hold and express a thought differ from the right to create a thought, being in control of the decision-making process and free from cognitive interferences operated by computational manipulation. Therefore, this paper argues in favour of recognising a newly emerged fundamental right, the right to mental self-determination, tailored to the unprecedented abilities of AI-driven manipulative technologies.